Wide-temperature low-loss MnZn ferrite soft magnetic material with intermediate-frequency characteristic and preparation method thereof
By optimizing the proportion of main and auxiliary components of MnZn ferrite soft magnetic materials and improving the preparation process, the problem of high losses of existing materials at medium frequency is solved, and low-loss and low-cost material preparation is achieved in a wide temperature range and medium frequency, adapting to the high frequency requirements of third-generation semiconductor devices.
Patent Information
- Application Number
- CN202411924976.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing MnZn ferrite soft magnetic materials have high losses at medium frequencies, making it difficult to meet the high frequency requirements of third-generation semiconductor devices such as GaN and SiC MOSFETs.
By optimizing the addition ratio of the main and auxiliary components and improving the preparation process, MnZn ferrite soft magnetic material with low loss at medium frequency of 200kHz to 300kHz was prepared. Specific measures include adjusting the ratio of Fe2O3, ZnO, MnO, increasing the addition of auxiliary components such as Co2O3, CaCO3, SiO2, and controlling the grain size and grain boundary resistance through the optimization of fine pulverization and sintering conditions.
The preparation of MnZn ferrite soft magnetic materials with low loss and low cost in wide temperature range and medium frequency is realized, which meets the needs of large-scale production and overcomes the problem of high loss of conventional ferrite materials at medium frequency.
Abstract
Description
Technical Field
[0001] The invention relates to the field of manganese-zinc ferrite magnetic materials, in particular to a medium-frequency characteristic, wide-temperature, low-loss MnZn ferrite soft magnetic material and a preparation method thereof. Background Art
[0002] With the development of semiconductors, the third-generation semiconductors (represented by GaN and SiC), also known as wide bandgap semiconductors, have a bandgap width of more than 2.2eV, and have the characteristics of high breakdown electric field, high saturation electron velocity, high thermal conductivity, high electron density, and high mobility, and are gradually gaining attention. Compared with the previous two generations of products, they have the advantages of high efficiency, high density, and high reliability, and are increasingly playing an important role in the fields of new energy vehicles, communications, and household appliances. The third-generation semiconductor devices replacing traditional silicon-based semiconductor devices is the future development direction. The demand for new soft magnetic power materials used to adapt to SiC and GaN MOSFETs is increasing. The operating frequency of traditional silicon-based MOSFETs is 100kHz or less. The operating frequency of power supplies using GaN and SiC MOSFETs is 200kHz to 300kHz. This urgently requires the rapid development of a wide-temperature, low-loss MnZn ferrite soft magnetic material that is suitable for third-generation semiconductors and has an operating frequency of 200kHz to 300kHz.
[0003] The loss of MnZn ferrite soft magnetic material can be divided into eddy current loss and hysteresis loss. At a frequency of 100kHz, the two account for 50% each. As the frequency increases, the eddy current loss will increase rapidly, while the hysteresis loss remains basically unchanged. In order to reduce the eddy current loss at medium frequency, it is necessary to reduce the eddy current inside the grains by refining the grain size; increase the grain boundary resistance by adjusting the addition ratio of auxiliary components to reduce the eddy current between the grains.
[0004] Prior art materials have lower losses at lower frequencies of 100 KHz, 200 mT, but their losses increase rapidly at medium frequencies of 200 KHz, 125 mT and 300 KHz, 100 mT.
[0005] In the document CN 112573912 A, a method for preparing a medium-wideband, wide-temperature, low-loss MnZn ferrite material is disclosed, which includes Fe2O3, MnO and ZnO as main components and additive auxiliary components, the molar percentage of the main components is: Fe2O3 is 52.5-53.5mol%, ZnO is 8.8-9.8mol%, MnO is the balance; according to the total weight of the main components, the content of each component of the additive auxiliary components is: CaCO3 is 0.04-0.06%, Nb2O5 is 0.02-0.03%, Co2O3 is 0.35-0.45%, ZrO2 is 0.01-0.03%, SiO2 is 30-120ppm, wherein the Si element is added in the form of nano-scale aerosolized SiO2. The method and materials used in the document have large losses during production, large costs, and more material waste, which reduces corporate profits.
[0006] Therefore, a new technical solution is needed to solve the above technical problems. Summary of the invention
[0007] In order to solve the above problems, the present invention discloses a medium-frequency characteristic, wide-temperature, low-loss MnZn ferrite soft magnetic material and a preparation method thereof, which can produce a MnZn ferrite material suitable for existing large-scale production with low loss and low cost in a wide temperature range and medium frequency. The material can overcome the shortcomings of conventional ferrite materials, has the characteristics of wide temperature, low loss, and low cost.
[0008] The technical solution of the present invention is: a medium-frequency characteristic, wide-temperature, low-loss MnZn ferrite soft magnetic material, comprising a main component and an auxiliary component; Calculated by weight percentage, the main components include: 71.3% to 71.6% Fe2O3, 6.0% to 6.4% ZnO, and 22.0% to 22.4% MnO; Calculated by weight percentage, the auxiliary components include: 0.3% to 0.5% Co2O3, 0.05% to 0.10% CaCO3, 0.005% to 0.02% SiO2, 0.02% to 0.04% Nb2O5, 0.05% to 0.20% NiO, 0.05% to 0.2% SnO2, and 0.01% to 0.03% ZrO2.
[0009] The medium frequency characteristics of the wide temperature and low loss MnZn ferrite soft magnetic material, the best main components are 71.45% Fe2O3, 6.25% ZnO and 22.3% MnO.
[0010] The preparation method of the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material comprises the following steps: Step 1: Mix and grind the main components: weigh the main components Fe2O3, MnO, and ZnO according to the proportion, and then put them into a ball mill for mixing and grinding; Step 2: Balling: Add 15% water to the powder obtained in step 1 to form small balls with a diameter of 5 to 8 mm; Step 3: Pre-sintering: Put the ball material produced in step 2 into a rotary kiln and pre-sinter it at 900-910°C for 1-2 hours; Step 4: Coarse crushing: put the pre-burned ball material in step 3 into a vibration mill for coarse crushing; Step 5: Fine grinding: Add pure water and auxiliary ingredients in proportion to the coarsely ground material in step 4 and grind it into fine powder using a sand mill; Step 6: Granulation and molding: Add 12% by weight of polyvinyl alcohol aqueous solution to the finely pulverized slurry in step 5 and mix evenly, then dry the slurry to granulate to obtain granules, and press the granules to form a ring-shaped green body; Step 7: Sintering: The obtained green body sample is placed in a bell furnace for sintering, with a heating rate of 2.0-2.2°C / min, a holding temperature of 1260°C, a holding time of 3.5-4.5 hours, an oxygen concentration Po2 of 4.5%-5.0%, and then cooled at a rate of 2.3-2.5°C / min under a balanced atmosphere to 980°C, and then cooled to room temperature in nitrogen at a cooling rate of 2.4-2.6°C / min; Step 8: Test: Use a soft magnetic material tester to perform loss detection on the sample ring of the sintered MnZn ferrite soft magnetic material.
[0011] Preferably, the grinding time using a ball mill in step 1 is 45-55 minutes.
[0012] By adopting the above technical solution, the particle sizes of the three raw materials are made more uniform, the consistency of the powder is improved, and the tap density of the powder is increased, which is more conducive to the next process of pelletizing.
[0013] Preferably, in step 2, water is added to the mixed powder to form small balls with a diameter of 5 to 8 mm.
[0014] By adopting the above technical solution, the raw material particles can be more tightly combined through this process, which is beneficial to improving the efficiency of the solid phase reaction between the three raw materials in the pre-firing stage.
[0015] Preferably, in step 5, the powder is finely ground by a sand mill for 110-130 minutes, and the particle size D50 value is required to be less than 1.6 microns.
[0016] By adopting the above technical solution, the reactivity of the granular material is increased by controlling the particle size of the fine powder, so as to achieve the effect of low-temperature sintering, thereby improving the performance and reducing energy consumption.
[0017] Preferably, in step 7, the final sintering holding temperature is 1250-1270° C., and the holding time is 3.5-4.5 hours.
[0018] By adopting the above technical solution, the growth rate of ferrite grains is controlled by adjusting the holding temperature and holding time during sintering, so that the grain size meets the requirements of this material, thereby achieving medium-frequency low-loss performance.
[0019] Preferably, the soft magnetic material tester in step 8 is a SY8218 instrument produced by Iwasaki Corporation of Japan.
[0020] The benefits of the present invention are as follows: 1. The present invention controls the addition range of the main component and the auxiliary component and improves the production process to obtain a wide-temperature MnZn ferrite soft magnetic material that meets the current large-scale production requirements under the medium frequency condition of 200kHz to 300kHz. The loss characteristics of this material are tested under the conditions of 200kHz and 125mT, and the loss at 25℃ is less than 270kw / m 3 , 60~120℃ loss is less than 320kw / m 3 ; Test the loss characteristics under 300kHz, 100mT conditions, the loss at 25℃ is less than 270kw / m 3 , 60~120℃ loss is less than 350kw / m 3 .
[0021] 2. The present invention can produce MnZn ferrite materials suitable for existing large-scale production at low loss and low cost in a wide temperature range and medium frequency. The material can overcome the shortcomings of conventional ferrite materials, has the characteristics of wide temperature and low loss, and is low in cost.
[0022] 3. The present invention optimizes the addition amount of auxiliary components such as CaCO3 and SiO2 to increase the resistance of the grain boundary, thereby suppressing the eddy current between the grains and reducing the eddy current loss between the grains.
[0023] 4. The present invention optimizes the sintering conditions, adjusts the sintering holding temperature and holding time, refines the grain size, and thus reduces the eddy current loss inside the grains. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Example
[0025] A medium-frequency, wide-temperature, low-loss MnZn ferrite soft magnetic material comprises a main component and an auxiliary component, wherein the main component comprises 71.55wt% Fe2O3, 22.31wt% MnO and 6.14wt% ZnO, and the auxiliary component comprises 0.08wt% CaCO3, 0.01wt% SiO2, 0.42wt% Co2O3, 0.025wt% Nb2O5, 0.015wt% ZrO2, 0.05wt% NiO and 0.1wt% SnO2. Example
[0026] A medium-frequency, wide-temperature, low-loss MnZn ferrite soft magnetic material comprises a main component and an auxiliary component, wherein the main component comprises 71.44wt% Fe2O3, 22.29wt% MnO and 6.27wt% ZnO, and the auxiliary component comprises 0.41wt% Co2O3. Other processes and small formulas are the same as those in Example 1. Example
[0027] A medium-frequency, wide-temperature, low-loss MnZn ferrite soft magnetic material comprises a main component and an auxiliary component, wherein the main component comprises 71.37wt% Fe2O3, 22.25wt% MnO and 6.38wt% ZnO, and the auxiliary component comprises 0.39wt% Co2O3. Other processes and small formulas are the same as those in Example 1.
[0028] The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material of the present invention comprises the following steps: Step 1: Use commercially available Fe2O3 with a purity of ≥99.3%, MnO with a Mn content of ≥76.6%, and ZnO with a purity of ≥99.7% as the main components, and mix Fe2O3, MnO, and ZnO in a ball mill in the amounts shown in Table 1. Then add water to the resulting powder at a ratio of 15% to form a small ball with a diameter of 8 mm, and pre-sinter at 905°C for 1.5 hours; Step 2: Put the pre-burned ball material into a vibrating mill for coarse crushing. Add pure water to the crushed material in proportion to make a slurry. At the same time, add auxiliary components in proportion: Ca2CO3, SiO2, Co2O3, Nb2O5, ZrO2, SnO2, etc. and crush them together through a sand mill. After the crushing is completed, add the binder polyvinyl alcohol solution in proportion; Step 3: Dry the slurry and granulate it evenly, and use a 40-ton dry powder press to press the granules into green sample rings; Step 4: The obtained green sample ring is placed in a bell furnace for sintering, with a heating rate of 2.1°C / min, a holding temperature of 1260°C, a holding time of 4.0 hours, an oxygen concentration Po2 of 4.7%, and then cooled at a rate of 2.4°C / min under a balanced atmosphere to 980°C, and then cooled to room temperature in nitrogen at a cooling rate of 2.5°C / min; Step 5: Use the SY8218 instrument produced by Iwasaki Corporation of Japan to perform a loss test on the sintered sample ring.
[0029] Table 1: Through the above process, 7 sets of power consumption Pcv data are obtained, as shown in Table 2.
[0030] Table 2: Conclusion: The data in Tables 1 and 2 show that: The main components and small formulas of Examples 1 to 3 are all within the scope defined by the present invention, and the material performance indicators fully meet the standards.
[0031] In Comparative Example 1, the Fe2O3 content is too low, resulting in insufficient compensation of the magnetocrystalline anisotropy constant K1, and the hysteresis loss in the low temperature section is too high, which cannot meet the performance requirements.
[0032] In Comparative Example 2, the Fe2O3 content is too high, resulting in excessive compensation of the magnetocrystalline anisotropy constant K1, which causes high hysteresis loss in the high temperature section and cannot meet the performance requirements.
[0033] In Comparative Example 3, the addition amount of CaCO3 and SiO2 in the small formula is insufficient, and the calcium silicate barrier formed at the grain boundary is not thick enough to effectively block the eddy currents between the grains, resulting in increased eddy current losses at medium and high frequencies in the material, which cannot meet the performance requirements.
[0034] In Comparative Example 4, the addition amount of CaCO3 and SiO2 in the small formula is too large, resulting in large-scale glass phase crystallization during sintering of the powder, destroying the spinel structure of the material and causing a sharp deterioration in performance.
[0035] The present invention controls the addition range of the main component and the auxiliary component and improves the production process to obtain a wide-temperature MnZn ferrite soft magnetic material that meets the current large-scale production requirements under the medium frequency condition of 200kHz to 300kHz. The obtained material can overcome the problem of high loss of conventional ferrite soft magnetic materials at a frequency of 200kHz to 300kHz, and has the characteristics of wide temperature and low loss.
[0036] It should be understood by those skilled in the art that the embodiments of the present invention described above are only examples and do not limit the present invention, and the purpose of the present invention has been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be modified or altered in any way without departing from the principles.
Claims
1. A medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material, comprising a main component and an auxiliary component, characterized in that: Calculated by weight percentage, the main components include: 71.3% to 71.6% Fe2O3, 6.0% to 6.4% ZnO, and 22.0% to 22.4% MnO; Calculated by weight percentage, the auxiliary components include: 0.3% to 0.5% Co2O3, 0.05% to 0.10% CaCO3, 0.005% to 0.02% SiO2, 0.02% to 0.04% Nb2O5, 0.05% to 0.20% NiO, 0.05% to 0.2% SnO2, and 0.01% to 0.03% ZrO2.
2. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 1, characterized in that: The following steps are involved: Step 1: Mix and grind the main components: weigh the main components Fe2O3, MnO, and ZnO according to the proportion, and then put them into a ball mill for mixing and grinding; Step 2: Balling: Add 15% water to the powder obtained in step 1 to form small balls with a diameter of 5 to 8 mm; Step 3: Pre-sintering: Put the ball material produced in step 2 into a rotary kiln and pre-sinter it at 900-910°C for 1-2 hours; Step 4: Coarse crushing: put the pre-burned ball material in step 3 into a vibration mill for coarse crushing; Step 5: Fine grinding: Add pure water and auxiliary ingredients in proportion to the coarsely ground material in step 4 and grind it into fine powder using a sand mill; Step 6: Granulation and molding: Add 12% by weight of polyvinyl alcohol aqueous solution to the finely pulverized slurry in step 5 and mix evenly, then dry the slurry to granulate to obtain granules, and press the granules to form a ring-shaped green body; Step 7: Sintering: The green sample was placed in a bell furnace for sintering at a heating rate of 2.0-2.2°C / min, a holding temperature of 1260°C, a holding time of 3.5-4.5 hours, an oxygen concentration Po2 of 4.5%-5.0%, and then cooled at a rate of 2.3-2.5°C / min under a balanced atmosphere to 980°C, and then cooled to room temperature in nitrogen at a cooling rate of 2.4-2.6°C / min; Step 8: Test: Use a soft magnetic material tester to perform loss detection on the sample ring of the sintered MnZn ferrite soft magnetic material.
3. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 2, characterized in that: The ball mill grinding time in step 1 is 45-55 minutes.
4. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 2, characterized in that: In step 2, water is added to the mixed powder to form small balls with a diameter of 5 to 8 mm.
5. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 2, characterized in that: In step 5, the powder is finely ground by a sand mill for 110-130 minutes, and the particle size D50 value is required to be less than 1.6 microns.
6. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 2, characterized in that: In the step 7, the final sintering holding temperature is 1250-1270° C., and the holding time is 3.5-4.5 hours.
7. The method for preparing the medium frequency characteristic wide temperature low loss MnZn ferrite soft magnetic material according to claim 2, characterized in that: The soft magnetic material tester in step 8 is the SY8218 instrument produced by Iwasaki Corporation of Japan.
Citation Information
Patent Citations
Preparation method of medium-broadband wide-temperature low-loss MnZn ferrite material
CN112573912A